Metabolomic profiling for the identification of novel diagnostic markers and therapeutic targets in prostate cancer: an update. (4th May 2019) - Lucarelli, Giuseppe; Loizzo, Davide; Ferro, Matteo; Rutigliano, Monica; Vartolomei, Mihai Dorin; Cantiello, Francesco; Buonerba, Carlo; Di Lorenzo, Giuseppe; Terracciano, Daniela; De Cobelli, Ottavio; Bettocchi, Carlo; Ditonno, Pasquale; et al.
ABSTRACT: Introduction : An altered metabolic regulation is involved in the development and progression of different cancer types. As well as this, many genes associated with tumors are shown to have an important role in control of the metabolism. The incidence of prostate cancer (PCa) is increased in men with metabolic disorders. In particular, obesity is an established risk factor for PCa. An increased body mass index correlates with aggressive disease, and a higher risk of biochemical recurrence and prostate cancer-specific mortality. Increased lipogenesis is also one of the most significant events in PCa metabolism reprogramming. Areas covered : In this article, we provide an updated review of the current understanding of the PCa metabolome and evaluate the possibility of unveiling novel therapeutic targets. Expert opinion : Obesity is an established risk factor for PCa, and an increased BMI correlates with aggressive disease, and a higher risk of biochemical recurrence and prostate cancer-specific mortality. PCa metabolome is characterized by the accumulation of metabolic intermediates and an increased expression of genes in the tricarboxylic acid cycle, the induction of de novo lipogenesis and cholesterogenesis. PCa cells can induce different alterations in their microenvironment by modulating the crosstalk between cancer and stromal cells.